Propensity to spend and borrow at a time of high pressure: the role of the meaning of Christmas and other psychological factors - McNair, Simon; Nyhus, Ellen K.; Ranyard, Rob (Frontiers in Behavioral Economics, 2024)
In countries where Christmas is celebrated, people are under pressure in the pre-Christmas period to spend on gift giving and socializing. In two surveys we investigated the role of the meaning of Christmas and other psychological factors in predicting propensity to spend and to borrow at Christmas (UK, N = 190; Norway, N = 234). Factor analysis identified three components of the meaning of Christmas: financial concerns, indulgence, and social aspects. In both surveys: (1) experienced financial hardship predicted lower propensity to spend and greater propensity to borrow;(2) more proactive money management practices predicted lower propensity to borrow; (3) material values predicted both propensity to spend and propensity to borrow; and (4) seeing Christmas as a time for indulgence, experiencing more negative affect, or less positive affect, predicted greater propensity to spend. Additionally: (1) in the UK survey, participants who said that lately they had been feeling more negative (more angry, sad etc.) had a greater propensity to borrow; and (2) in the Norway survey, an obligation gift motivation predicted propensity to spend. The findings show that in addition to experienced financial hardship and proactive money management practices, the psychological factors of material values, affect, and gift motivation play significant roles in propensity to spend and/or borrow at this time of high pressure. We discuss implications for theory and financial interventions.